Serotonin secretion and metabolism in postmenopausal women with gastrointestinal functional disorders - Wiśniewska-Jarosińska, Maria; Klupińska, Grażyna; Kulig, Grażyna; Walecka-Kapica, Ewa; Chojnacki, Cezary (Menopause Review/Przegląd Menopauzalny, 2009)
In postmenopausal women ailments of the gastrointestinal tract often occur. Pathogenesis of these disorders is complex and remains to a large extent unknown. It has been suggested that one of the factors to be considered may be an impaired homeostasis of serotonin. Aims: The study aimed at evaluating serotonin secretion and urinary excretion of its major metabolite – 5-hydroxyindole acetic acid in pre- and postmenopausal women. Materials and methods: The study comprised 50 women, aged 55–63 years (mean age 57.3 ±3.9), from two to twelve years after the last menstruation and 25 clinically healthy women – the control group (K), aged 29–36 years. In 25 of the studied patients functional dyspepsia (FD) was diagnosed, and in the other 25 functional constipation (FS). The diagnoses were based on the Rome III Criteria. Serotonin serum concentration and 5-hydroxyindole acetic acid in urine were measured by ELISA method applying IBL antibodies. Results: Serotonin serum concentration was as follows: in the controls (K) – 163.52 ±29.39 ng/ml, in women with FD – 136.15 ±27.58 ng/ml (p < 0.001) and in those with FC – 139.67 ±21.40 ng/ml (p < 0.01). The amount of 5-hydroxyindol acetic acid in urine collection was respectively: K – 5.77 ±2.33 mg/24 h, FD – 3.15 ±2.52 mg/24 h (p < 0.01), FC – 4.00 ±2.13 mg/24 h (p < 0.05). The results obtained of both measured parameters negatively correlated with the symptoms severity. Conclusions: 1. Serotonin secretion in women in the postmenopausal period is decreased. 2. Relative depletion of serotonin may be the cause of functional disorders of the gastrointestinal tract.